Accuracy of the Obstetric Early Warning System in Predicting Maternal Morbidity: Systematic Literature Review - Cicilia, Fitri; Runjati, Runjati; Latifah, Leny; Idayati, Idayati; Kusumawati, Dwi Erma (Poltekkes Kemenkes Palu, 2025)
Background: The Obstetric Early Warning System does not seem to be well known among health workers, especially midwives. One way to prevent maternal mortality, which is quite high in Indonesia, is to prevent delays in diagnosis through appropriate screening, thereby enabling quicker treatment, thus resulting in a reduction in cases of maternal mortality. This study tries to discuss the evidence regarding the application of the Obstetric Early Warning System by showing its accuracy in predicting maternal morbidity. Method: A systematic Literature Review is the right choice to collect the latest evidence. Search for articles through electronic browser databases, namely Pubmed and Google Scholar. This browser was chosen because it was considered to have a more complete source based on the research topic, namely obstetric early warning. The key words used are MOEWS, MEWT, MEWC, MEWS in the period 2013-October 2023. Results: A total of 2647 articles were obtained but only 8 selected articles were discussed because they met the inclusion and exclusion criteria. Early warning in obstetric patients evaluated in this study consisted of SOS, MOEWS, MEWT, SI, e-CART, MEWC, and MEWS. Conclusion: The obstetric early warning system can predict maternal morbidity, although the level of accuracy varies. All early warning systems always begin with checking vital signs so the assessment needs to be carried out carefully to initiate immediate action if necessary.